Penerapan Pembelajaran Berdiferensiasi Untuk Meningkatkan Motivasi Belajar Siswa Kelas II Materi Lingkungan Sehat Dan Tidak Sehat - Laela Putri, Annisa; Mujahidah , Idah; Malini , Serli; Prihantini , Prihantini (PT. ALHAFI BERKAH INDONESIA, 2023)
Abstract. The diversity of students' potential and interests, especially in learning Natural Sciences (Science), emphasizes the need for innovation in learning to increase learning motivation. One effort that can be made is through the application of differentiated learning. The aim of writing this article is to increase understanding of the application of differentiated learning in the context of healthy and unhealthy environmental material. The research method used is descriptive with a literature study approach, by collecting information from various sources and the results of research reviews that are relevant to the topic discussed. The results of this research show that differentiated learning can be divided into two stages. The first stage is pre-implementation of learning by conducting diagnostic tests to assess student understanding. The second stage is the implementation of learning by dividing students into different groups based on the results of the diagnostic test, taking into account the characteristics found. This is done to ensure that each group gets a learning approach that suits their needs. Through this research, it is hoped that it can provide a clearer picture regarding the implementation of differentiated learning in learning about healthy and unhealthy environments.